Model Simulation Approach for Exploring Profitability of Small-scale Cavendish Banana Farmers in Davao Region from Harvest Allocation to Enterprises. - Mata, May Anne E.
Changes that occurred in the agriculture-food system ? for instance, increase in disease incidence compounded by climate change, as well as changes in contractual arrangements and policies ? pose challenges to small-scale Cavendish banana farmers in the Davao region, the top producer of Cavendish in the Philippines, in terms of their vulnerability and ability to survive. The current challenges can be addressed by increasing the opportunity of small-scale farmers to increase their profit by exploring alternative enterprises. The current system of the farmers is to allocate their entire harvested Cavendish bananas into the contractual market or the spot market. While these farmers can improve their profit by processing raw bananas into alternative products such as banana flour, very few of them have embarked on this enterprise. One reason for this is the limited understanding of this market potential and its profitability relative to contractual or spot market. Hence, in this study, we explored through a model simulation ? a novel yet simplistic approach ? different scenarios of a farmer?s profit as they venture into the banana flour market. Some model considerations include flour demand, the volatility of spot market prices, and banana production rates. Our simulations show that the total profit of the model farmer varies significantly with different allocations of bananas to contractual or spot markets for various demands in the banana flour market. Additionally, with our model assumptions, model farmers can further increase their profit if all their unsold fresh bananas have been processed to banana flour and sold them during high demand. Finally, we highlight the novelty of our approach as a diagnostic tool to initially assess the profitability of a commodity among different market options especially when there are unexplored scenarios and data is scarce.
Keywords: Science -- Periodicals; Small-scale farmer; Cavendish banana flour; Harvest allocation; Profitability; Simulation; Contractual farm